Pengaruh Strategi Penerimaan Pajak Kendaraan Bermotor (PKB) Dalam Peningkatan Pendapatan Asli Daerah Pada Samsat Gerung - Aryani, R . Ayu Ida; Muliani, Muliani; Azzahra, Baiq Shelia Rara (Universitas Mataram, 2024)
This study aims to analyze the effect of socialization strategies, field raids, and mobile Samsat services on increasing Regional Original Income (PAD) at Samsat Gerung. Using a quantitative approach with an associative design, this research involved 51 respondents selected through a saturated sampling technique. Data were analyzed using multiple linear regression. The results indicate that socialization strategies, field raids, and mobile Samsat services do not significantly impact PAD improvement. Internal factors such as taxpayer awareness and external factors like economic constraints and service access influence strategy effectiveness. These findings suggest the need to enhance socialization strategies through innovative communication, improve mobile Samsat services with digital solutions, and enforce stricter penalties to boost taxpayer compliance. This study contributes to the evaluation of vehicle tax management policies in supporting PAD growth.